2023
DOI: 10.1039/d3dt00889d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of ruthenium complexes bearing the 1,2,4-triazole group as potential membrane-targeting antibacterial agents towards Staphylococcus aureus

Abstract: Bacterial infection was one of the most serious public health problems, harmful to human health and cost a lot. Nowadays, misuse and overuse of antibiotics have led to the emergence...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…As previously reported, complexes containing methyl or tert -butyl groups may exhibit enhanced antimicrobial activity against S. aureus . 39–46 Surprisingly, the MIC values under dark and light conditions did not show substantial variation, and it is speculated that the low dose of ruthenium complexes may not be sufficient to entirely inhibit the growth of bacteria and the inherent dark toxicity of this series of complexes against S. aureus . It can be observed that the MBC values of Ru1–Ru8 show significant changes before and after optical exposure, indicating that ruthenium complexes have photo-inactivation effects on S. aureus under blue light irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…As previously reported, complexes containing methyl or tert -butyl groups may exhibit enhanced antimicrobial activity against S. aureus . 39–46 Surprisingly, the MIC values under dark and light conditions did not show substantial variation, and it is speculated that the low dose of ruthenium complexes may not be sufficient to entirely inhibit the growth of bacteria and the inherent dark toxicity of this series of complexes against S. aureus . It can be observed that the MBC values of Ru1–Ru8 show significant changes before and after optical exposure, indicating that ruthenium complexes have photo-inactivation effects on S. aureus under blue light irradiation.…”
Section: Resultsmentioning
confidence: 99%